Early China coast meteorology : the role of Hong Kong - MacKeown, P. K. (Royal Asiatic Society Hong Kong studies series., 2010)
Numerous personality clashes and financial and other intrigues surrounded the early efforts to set up an Observatory in Hong Kong. Blending personalities, politics and practicalities of studying the weather, this entertaining book provides valuable and informative insights into the public and private controversies growing out of responses to and responsibilities involved in the protection of life and property. This portrait is set firmly in the context of the history of Hong Kong as British colony on the China Coast and its role as a burgeoning commercial port within the trading complex of the Empire. It brings to life many of the people and institutions in Hong Kong and elsewhere on the development of meteorology on the China Coast.